Sonographic imaging features of alveolar soft part sarcoma: Case series and literature review. Issue 46 (18th November 2022) - Li, Wenxue; Zhang, Shanshan; Fan, Wenting; Li, Diancheng; Tian, Hui; Che, Dongdong; Yu, Lei; Gao, Shuang; Liu, Yiqun
Abstract : Background: Alveolar soft part sarcoma (ASPS) is a rare tumor but potentially fatal condition. Understanding the imaging and clinical features of ASPS is of certain value for preoperative qualitative diagnosis and clinical treatment of tumors. Nevertheless, there have been only 11 documented case reports describing the sonographic features in the English literature. Methods: Three patients with confirmed ASPS occurring primarily in the limbs were enrolled in this study. Complete surgical excision was performed with conservative limb function. We pay particular attention to the ultrasonographic features and performed a literature review of ASPS cases. Results: With regular surveillance, one patient had no symptom recurrence and two developed lung and/or breast metastasis later. The specific sonographic findings were heterogeneous hypoechoic, well-circumscribed, and lobulated or round contours on grayscale images, abundant flow signals of intratumoral and extratumoral tubular structures on color Doppler images. Conclusion subsections: Its low incidence rate and lack of characteristic clinical manifestations often result in misdiagnosis of ASPS. The specific sonographic findings may add useful diagnostic information.